PENGARUH PERILAKU BIROKRASI TERHADAP PELAYANAN PUBLIK DI DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Ulfa Rafika Fajriah; Muhammad Rais Rahmat Razak (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Abstract This study aims to determine whether bureaucratic behavior and public services have a significant influence in the Timoreng Panua Village, Sidenreng Rappang Regency.The population of this study is the whole community who received service in the village of Timoreng Panua, Sidenreng Rappang district, as for the population taken from November 2018 - January 2019, totaling 57 people. The sample in this study is saturated sampling. This type and type of research is quantitative descriptive. Data collection techniques used in this study are Observation, Documentation, Questionnaire, Library Study. The collected data was then analyzed using frequency tabulation analysis and SPSS 16.0. The results of this study for indicators of Bureaucratic Behavior show 61.9% of the amount of data produced is in the "good" category. And on the Public Service indicator shows 64.84% of the amount of data produced is in the "good" category. Based on the results of bureaucratic behavior towards public services in the Timoreng Panua village office in Sidenreng Rappang Regency, it has an influence of 24.0% with the category "less good".